2008
DOI: 10.1002/hep.22090
|View full text |Cite
|
Sign up to set email alerts
|

Serum aminotransferase activity and mortality risk in a United States community

Abstract: Serum aminotransferase [such as aspartate aminotransferase (AST) and alanine aminotransferase (ALT)] is commonly used as an indicator of liver disease. The aim of the study was to determine the degree to which aminotransferase results are associated with increased mortality at the population level. All adult residents of Olmsted County, Minnesota, who had a health care encounter at Mayo Clinic, Rochester, in 1995 were identified and their AST or ALT results extracted from a laboratory database. These subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
2
9

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(152 citation statements)
references
References 29 publications
6
135
2
9
Order By: Relevance
“…In patients with liver disease, elevated ALT levels may be related to sex (higher in men), body mass, metabolic syndrome, nonalcoholic steatohepatitis, chronic alcohol consumption, or co-existing hepatitis C infection and may be associated with increase mortality risk. 26,29 In our patients herein, we excluded HBsAg-positive patients who had co-existing liver disease such as alcoholic liver disease, autoimmune hepatitis, hemochromatosis, nonalcoholic steatohepatitis, and chronic HCV infection. However, most patients with chronic hepatitis B will experience viral and biochemical flares that result in increases in the serum ALT and aspartate aminotransferase values.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with liver disease, elevated ALT levels may be related to sex (higher in men), body mass, metabolic syndrome, nonalcoholic steatohepatitis, chronic alcohol consumption, or co-existing hepatitis C infection and may be associated with increase mortality risk. 26,29 In our patients herein, we excluded HBsAg-positive patients who had co-existing liver disease such as alcoholic liver disease, autoimmune hepatitis, hemochromatosis, nonalcoholic steatohepatitis, and chronic HCV infection. However, most patients with chronic hepatitis B will experience viral and biochemical flares that result in increases in the serum ALT and aspartate aminotransferase values.…”
Section: Discussionmentioning
confidence: 99%
“…In population studies, high ALT level is associated with increased risk of liver-related and cardiovascular mortality. 10,11 On the other hand, it remains unclear how clinicians should interpret ALT results in NAFLD patients. First, the normal range of ALT is derived from healthy subjects in the general population.…”
mentioning
confidence: 99%
“…NAFLD and cardiovascular disease risk factors: Elevated serum ALT (or suspected fatty liver disease) is associated with increased risk of cardiovascular and all-cause mortality (in addition to liver mortality) in adults (34). A case-control study from our group showed that children with biopsy proven NAFLD were more likely to have dyslipidemia, hypertension, insulin resistance, and more components of metabolic syndrome than age-sex-BMI matched controls without NAFLD (35).…”
Section: Clinical-pathologic Correlationmentioning
confidence: 83%